Guest List Management Information System in the Working Area of the Central Statistics Agency - Mesanda, Zery; Taufik Al Afkari Siahaan, Ahmad (Journal of Computer Science and Informatics Engineering, 2023)
The Guest List Management Information System in the working area of the Central Statistics Agency has become the main center for this practical work plan. Based on the desire to advance operational efficiency and maximize services to visitors, this motorbike taxi aims to design and implement an integrated system for managing guest lists within the BPS environment. Important findings prove that an integrated Guest List Management Information System can increase operational efficiency, increase data security, and strengthen ties between BPS and various visiting departments. This project was created based on unfavorable conditions for visiting guests and to develop better relations with visitors from various groups. Thus, this project not only shares a broad view of the importance of an effective information system in managing the guest list at BPS, but also provides certain recommendations for streamlining the existing system to improve the institution's capabilities and interaction with visitors